Add-on Psoralea corylifolia mother tincture external application to individualized homeopathic medicines in treatment of vitiligo: Open, randomized, pragmatic, pilot trial. Issue 1 (March 2022) - Mir, Anaitulah Ahmad; Wani, Ghulam Nabi; Prajapati, Ramkripal; Saklani, Nitin; Karuppusamy, Avaranjika; Jha, Pankaj Kanti; Chattopadhyay, Abhijit; Nayak, Chintamani; Paul, Swapan; Ali, Sk. Swaif; Koley, Munmun; Saha, Subhranil
Abstract: Background: Vitiligo causes patchy hypo-pigmentation of skin and mucous membrane, with cosmetic and psychological effects. Studies suggest Psoralea corylifolia (PC) has pigmentor properties and that individualized homeopathic medicines (IH) are a promising treatment option in vitiligo. This pilot trial was aimed at testing the feasibility of a future definitive trial comparing the effects of three treatment regimens – 1. IH, 2. PC mother tincture (MT) external application, and 3. IH and PC (IHPC) in the treatment of vitiligo. Methods: An open, randomized (1:1:1), three parallel arms, pragmatic, pilot trial was conducted on 60 patients at the dermatology and Materia Medica outpatients of National Institute of Homoeopathy (NIH), India. Primary outcome was Vitiligo Area Scoring Index (VASI); and secondary outcomes were Vitiligo Quality of Life (VitiQoL) and Dermatological Life Quality Index (DLQI); assessed at baseline, 3rd month and 6th month. Intention-to-treat analysis was performed; intra-group and inter-group comparisons were made by Friedman and Kruskal-Wallis tests respectively. Results: Five patients dropped out (IH: 2, PC: 2, IHPC: 1). Intra-group changes over 3 and 6 months were mostly statistically significant in all 3 outcomes ( P < 0.001). No significant differences were observed in VASI and DLQI total scores among the three groups over either 3 or 6 months. Differences among groups after 3 and 6 months showed statistical significances in VitiQoL total scores ( P = 0.038 and 0.037 respectively) favoring PC and IHPC respectively. Conclusion: A definitive trial appears feasible. All three regimens appeared equally effective and safe, though a small positive direction of effect towards PC and IHPC was observed. As a pilot trial, no definite conclusions could be drawn. Trial registration: CTRI/2018/04/013446.